2019
DOI: 10.1177/0278364919868017
|View full text |Cite
|
Sign up to set email alerts
|

Robotic pick-and-place of novel objects in clutter with multi-affordance grasping and cross-domain image matching

Abstract: This paper presents a robotic pick-and-place system that is capable of grasping and recognizing both known and novel objects in cluttered environments. The key new feature of the system is that it handles a wide range of object categories without needing any task-specific training data for novel objects. To achieve this, it first uses an object-agnostic grasping framework to map from visual observations to actions: inferring dense pixel-wise probability maps of the affordances for four different grasping primi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
148
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(168 citation statements)
references
References 50 publications
(111 reference statements)
1
148
0
Order By: Relevance
“…Also, the availability of affordable RGB-D sensors enabled the use of deep learning techniques to learn the features of objects directly from image data. Recent experimentations on Convolutional neural network [2], [17], [18] have demonstrated that they can be used to efficiently compute stable grasps, Pinto et al [3] used an architecture similar to AlexNet to depict that by increasing the size of the data, their CNN was able to generalize better to new data. Varley et al [19] propose an interesting approach to grasp planning through shape completion where a 3D CNN was used to train the network on 3D prototype of objects in their own dataset captured from various viewpoints.…”
Section: Related Workmentioning
confidence: 99%
“…Also, the availability of affordable RGB-D sensors enabled the use of deep learning techniques to learn the features of objects directly from image data. Recent experimentations on Convolutional neural network [2], [17], [18] have demonstrated that they can be used to efficiently compute stable grasps, Pinto et al [3] used an architecture similar to AlexNet to depict that by increasing the size of the data, their CNN was able to generalize better to new data. Varley et al [19] propose an interesting approach to grasp planning through shape completion where a 3D CNN was used to train the network on 3D prototype of objects in their own dataset captured from various viewpoints.…”
Section: Related Workmentioning
confidence: 99%
“…For semantic occlusion segmentation, we extend previous work of semantic (visible) segmentation by fully convolutional networks (FCN) proposed in [1]. All layers are composed of convolutional or pooling layers, which keep the geometry of image, so FCN is known as effective and widely used for pixel-wise score regression tasks: depth prediction [24,25], grasp affordance [12,26,27], optical flow [28], and instance masks [4,6].…”
Section: B Semantic Occlusion Segmentationmentioning
confidence: 99%
“…One prominent field is robotic manipulation, in which industrial parts are grasped and are placed to a desired location [62], [56], [57], [60], [91], [202], [200]. Amazon Picking Challenge (APC) [1] is an important example demonstrating how object detection and 6D pose estimation, when successfully performed, improves the autonomy of the manipulation, regarding the automated handling of parts by robots [55], [58], [59]. Household robotics is another field where the ability of recognizing objects and accurately estimating their poses is a key element [97], [98], [99].…”
Section: Introductionmentioning
confidence: 99%